HAJI DAN KEGAIRAHAN EKONOMI:: Menguak Makna Ibadah Haji Bagi Pedagang Muslim di Yogyakarta - M. Sulthoni; Muhlisin; Muthoíin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
Haj is an exclusive and unique worship. It is exclusive because not all Muslims do not have to that. This ritual is only done by those who have the physical ability, psychological, and financial requirements to run it. Hajj ritual is unique because it often goes beyond the normative boundaries. The phenomenon of pilgrimage draper in Beringharjo market that is the subject of this study clearly demonstrate this. The traders set aside a portion of the liver berrela trading profits earned every day, collecting little by little in a long time, and after a relatively large collected was not used to expand the business as usual by merchants, but